2021
DOI: 10.4183/aeb.2021.207
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Parathyroidectomy During Total Thyroidectomy as a Possible Risk Factor of Hypocalcemia. Experience of a Single Center and Review of Literature

Abstract: Context. Post-operative clinical and biochemical hypocalcemia is a common complication of thyroid surgery and the correlation with incidental parathyroidectomy (IP) remains controversial.Objective. To evaluate the incidence of IP during TT, its correlation to early post-surgery hypocalcemia, and its potential risk factors.Patients and Methods. 77 consecutive patients submitted to thyroid surgery between January 2018 and December 2019. Demographic, clinical, biochemical, surgical and histopathological factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In addition, studies have reported that removing one or two glands does not significantly affect PH. 11 , 26 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have reported that removing one or two glands does not significantly affect PH. 11 , 26 , 39 …”
Section: Discussionmentioning
confidence: 99%